Effects of Different Strain Rates on the Impact Properties of Recycled Aggregate Concrete Modified With Nanosilica Solution and Polyvinyl Alcohol Fiber - Wang, Xingguo; Jiang, Maolin; Zhang, Xianggang; Cheng, Zhaoxia; Gong, Jian; Cheng, Fei (Frontiers in Materials, 2021)
The recycled aggregate (RA) was modified by 2% nanosilica solution, and the split Hopkinson pressure bar (SHPB) test device was used to study the dynamic impact properties of the modified recycled aggregate concrete (RAC) mixed with polyvinyl alcohol (PVA) fibers. The RA replacement percentage, the amount of PVA fiber, and the strain rate were variables. The failure pattern, the stress–strain curve of the nanosilica solution, and PVA fiber-modified RAC were shown under different strain rate conditions. Dynamic peak stress, peak strain, and dynamic increase factor (DIF) of the specimens are discussed. The results showed that the stress and dynamic peak strain value of the specimen increased with the increase of the strain rate; moreover, with the increase of the RA replacement percentage and the PVA fiber content, the dynamic peak stress of the specimen decreases, while the dynamic peak strain and the DIF value increase. The incorporation of nanosilica-modified RA is beneficial to the improvement of the impact performance of RAC, and the incorporation of an appropriate amount of the PVA fiber effectively improves the deformability of RAC.